Human T cell leukaemia virus type 2 tax protein mediates CC-chemokine expression in peripheral blood mononuclear cells via the nuclear factor kappa B canonical pathway. (3rd December 2013) - Barrios, C S; Castillo, L; Zhi, H; Giam, C-Z; Beilke, M A
Summary: Retroviral co-infections with human immunodeficiency virus type-1 (HIV-1) and human T cell leukaemia virus type 1 (HTLV-1) or type 2 (HTLV-2) are prevalent in many areas worldwide. It has been observed that HIV-1/HTLV-2 co-infections are associated with slower rates of CD4 + T cell decline and delayed progression to AIDS. This immunological benefit has been linked to the ability of Tax2, the transcriptional activating protein of HTLV-2, to induce the expression of macrophage inflammatory protein (MIP)-1α/CCL3, MIP-1β/CCL4 and regulated upon activation normal T cell expressed and secreted (RANTES)/CCL5 and to down-regulate the expression of the CCR5 co-receptor in peripheral blood mononuclear cells (PBMCs). This study aimed to assess the role of Tax2-mediated activation of the nuclear factor kappa B (NF-κB) signalling pathway on the production of the anti-viral CC-chemokines MIP-1α, MIP-1β and RANTES. Recombinant Tax1 and Tax2 proteins, or proteins expressed via adenoviral vectors used to infect cells, were tested for their ability to activate the NF-κB pathway in cultured PBMCs in the presence or absence of NF-κB pathway inhibitors. Results showed a significant release of MIP-1α, MIP-1β and RANTES by PBMCs after the activation of p65/RelA and p50. The secretion of these CC-chemokines was significantly reduced ( P  < 0·05) by canonical NF-κB signalling inhibitors. In conclusion, Tax2 protein may promote innate anti-viral immune responses through the activation of the canonical NF-κB pathway.